Second cancers and causes of death in patients with testicular cancer in Sweden - Zhang, Luyao; Hemminki, Otto; Chen, Tianhui; Yu, Hongyao; Zheng, Guoqiao; Chattopadhyay, Subhayan; Försti, Asta; Sundquist, Kristina; Sundquist, Jan; Hemminki, Kari (PLOS ONE, 2019)
While treatment for testicular cancer (TC) has become standardized after the 1980s with an associated significant improvement in patient survival, this has been accompanied by an increased risk of second primary cancers (SPCs). Patients were identified from the Swedish Cancer Registry spanning the years from 1980 to 2015, including 8788 individuals with primary TC and their SPCs. Relative risks (RRs) for SPC were calculated using the generalized Poisson regression model. SPCs were diagnosed in 9.4% of patients with TC and half of them were late onset cancers not common in the population in their 40s. Overall RR of SPCs (excluding second TC) was 1.30 (95%CI: 1.20-1.40), including high risks for seven solid cancers, non-Hodgkin lymphoma and leukemia. Second TC was the most common SPC and the RR of 17.19 (95%CI: 14.89-19.85) was the highest recorded. Cancers known to be fatal as first primary cancers were also fatal as SPC in TC patients. Survival at 30 years of follow-up was approximately 80% for TC patients without SPC but it decreased to 40% for patients with SPC. The unexpected finding that half of the identified SPCs were typical late onset cancers in the middle-aged population raises concerns that therapy may facilitate premature aging. The risks of SPC are clinically important for the long-term management of TC patients and the high-mortality calls for a future management strategy.
Gesehen am 31.07.2019